Assessment of the Efficacy of Virtual Reality Rehabilitation in Stroke Patients - Faisal Nabi Depar, Ata Ur Rehman, Tauseef Raza, Adnan Mahmood, Saeed Taj Din (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Stroke is still one of the most prominent causes of adult disability globally and often results in both long-term physical and cognitive impairments. While traditional rehabilitation methods do have some effectiveness, they are sometimes hampered by low engagement and adherence levels from the patients. The use of virtual reality technology (VR) offers a new way to approach rehabilitation which could result in better outcomes because it creates an immersive experience that is inherently interactive. This study aimed to assess the effectiveness of VR-based rehabilitation in improving motor function, functional independence, and cognitive performance in stroke patients, compared with traditional therapy. Methods: Seventy-one stroke patients participated in the study and were randomized into two groups: one receiving virtual reality rehabilitation and the other receiving standard physiotherapy as a control arm to conventional treatment. The therapies were both provided over a six-week period, five days per week. The primary outcome measures were Fugl-Meyer Assessment and Barthel Index. Other outcome measures included cognitive assessment using Montreal Cognitive Assessment (MoCA), mobility measured by Timed Up and Go (TUG) test, and satisfaction level reported by the patients which were all considered as secondary outcomes. Results: Participants in the VR group demonstrated significantly greater improvements in motor function and independence in daily activities compared to the control group (p < 0.01). Cognitive gains were higher in the VR group, although this did not reach statistical significance (p = 0.058). Patient adherence and satisfaction were notably higher among VR participants. Conclusion: VR-based rehabilitation is a promising and effective approach to enhance post-stroke recovery, offering better patient outcomes and engagement than conventional methods. Further large-scale studies are recommended to confirm these findings and explore long-term effects. Keywords: Stroke rehabilitation, virtual reality therapy, motor recovery, cognitive function, patient engagement, Fugl-Meyer, Barthel Index.